Genetic Divergence Studies for the Quantitative Traits of Paddy Under Coastal Saline Eco System - ANURADHA , T.; RAO, K. NAGENDRA (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Soil salinity is a global phenomenon adversely affecting the productivity of millions of hectares of land, compromising the ability of a large number of countries to maintain the agricultural production and productivity targets. Salt tolerance of a plant varies with environmental and biological factors and response to salinity in terms of morphology, anatomical adoption and changes in various physiological and biochemical processes under salt stress facilitate the formulation of agro techniques and development of salt tolerant varieties through conventional, as well as, biotechnological approaches. Generally, salinity tolerance is a polygenic trait. Screening rice germplasm to locate salt tolerant genes for use in improving the currently grown varieties is of continuous importance to plant biotechnologists (Flowers, 2004). One major approach in plant breeding is to maximize the genetic diversity between parental genotypes for hybridization. There are rice varieties which yield high under normal condition; they fail to perform in salt affected soils. So, genetic diversity screening for trait of interest is an essential part of the commencement of a breeding program